2022
DOI: 10.3389/fpsyt.2022.927540
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment increases the suicidal risk in Chinese schizophrenia patients

Abstract: ObjectivesChildhood trauma might be a modifiable risk factor among adults with serious mental illness. However, the correlation of child trauma and suicide is unclear, which were cited most frequently as the biggest challenge to schizophrenia (SCZ) patients in China. We aim to study relationships between child trauma and suicide in SCZ patients of different disease stages.MethodsNinety-one participants were included and divided into two groups, namely, first-episode group (n = 46), relapsed group (n = 45). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The old SZ patients perceive and adjust to their illnesses well [ 41 ], which might be used to explain the low prevalence of suicidal ideation in the middle-aged and elderly patients. Meanwhile, high BMI was found to be a risk factor for suicidal ideation in the middle-aged and elderly patients, which is consistent with the previous study [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…The old SZ patients perceive and adjust to their illnesses well [ 41 ], which might be used to explain the low prevalence of suicidal ideation in the middle-aged and elderly patients. Meanwhile, high BMI was found to be a risk factor for suicidal ideation in the middle-aged and elderly patients, which is consistent with the previous study [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in agreement with other studies that have shown that childhood trauma is an important predictor of worse treatment outcomes, lower compliance rates and reduced social functioning in patients with psychotic and non-psychotic mental disorders. [3,5,9,30,50,51] The same can be connected with the high degree of individual and systemic traumatization that the parents of the participants experienced during the 5-year period of the civil war that was held in this area 3 decades ago. [34] It should be noted that a significant percentage of the participants in this study, during the period of war, were in childhood and adolescent development (26.7%) and were presumably exposed to frequent emotional abuse and often witnessed domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with other studies that have shown that childhood trauma is an important predictor of worse treatment outcomes, lower compliance rates and reduced social functioning in patients with psychotic and non-psychotic mental disorders. [ 3 , 5 , 9 , 30 , 50 , 51 ] The same can be connected with the high degree of individual and systemic traumatization that the parents of the participants experienced during the 5-year period of the civil war that was held in this area 3 decades ago. [ 34 ]…”
Section: Discussionmentioning
confidence: 99%
“… 12 Another study in individuals with relapse schizophrenia demonstrated that suicide ideation could be related to emotional neglect and sexual abuse, while suicide ideation was not associated with other types of childhood maltreatment. 6 The different sample characteristics and relatively small sample sizes ( N = 50–313) in previous studies might contribute to these inconsistencies.…”
Section: Association Between Childhood Maltreatment and Suicidality I...mentioning
confidence: 97%
“…First, previous studies have produced highly varied results. [6][7][8][9][10][11][12][13] Several studies reported no association between childhood maltreatment and suicide ideation in people with chronic schizophrenia 10 or people with first-episode schizophrenia, 6 while other studies demonstrated a positive relationship. 7,11 Second, previous research has identified varying associations between specific types of childhood maltreatment, i.e.…”
Section: Association Between Childhood Maltreatment and Suicidality I...mentioning
confidence: 99%